2017
DOI: 10.1111/add.13764
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and primary prevention in people who inject drugs for chronic hepatitis C infection: is elimination possible in a high-prevalence setting?

Abstract: Aims To project the impact of scaling up oral antiviral therapy and harm reduction on chronic hepatitis C (CHC) prevalence and incidence among people who inject drugs (PWID) in Greece, to estimate the relationship between required treatment levels and expansion of harm reduction programs to achieve specific targets and to examine whether hepatitis C viruse (HCV) elimination among PWID is possible in this high prevalence setting. Design A dynamic discrete time, stochastic individual-based model was developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 51 publications
(50 reference statements)
3
35
0
2
Order By: Relevance
“…Subsequent studies have explored the potential of HCV treatment as prevention among PWID populations in a range of settings including North America, Europe, Asia and Australia . Broadly speaking, these studies have generally found that scale up of HCV treatment to rates to below 100 per 1000 PWID annually, particularly in combination with harm reduction , can reduce HCV incidence by 90% by 2030 across a wide range of settings. Results have been consistent between high and low income settings examined, such as Vietnam .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent studies have explored the potential of HCV treatment as prevention among PWID populations in a range of settings including North America, Europe, Asia and Australia . Broadly speaking, these studies have generally found that scale up of HCV treatment to rates to below 100 per 1000 PWID annually, particularly in combination with harm reduction , can reduce HCV incidence by 90% by 2030 across a wide range of settings. Results have been consistent between high and low income settings examined, such as Vietnam .…”
Section: Resultsmentioning
confidence: 99%
“…Several initial modelling studies in the UK and general PWID populations of varying prevalences have indicated that harm reduction alone is unlikely to achieve HCV elimination among PWID populations [13,14]. Subsequent studies have explored the potential of HCV treatment as prevention among PWID populations in a range of settings including North America, Europe, Asia and Australia [13,[15][16][17][18][19][20]. Broadly speaking, these studies have generally found that scale up of HCV treatment to rates to below 100 per 1000 PWID annually, particularly in combination with harm reduction [13,16,21], can reduce HCV incidence by 90% by 2030 across a wide range of settings.…”
Section: Hiv-infected Pwidmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Health Organization Global Health Sector Strategy (GHSS) on Viral Hepatitis has set a challenging goal of eliminating viral hepatitis as a major public health threat by 2030, reducing new chronic infections by 90% and mortality by 65%. In most countries these targets can be achieved only through scaling-up both OST, NSP and HCV treatment for PWID, as highlighted in a recent paper (the first in our series) on HCV in Greece [19]. Another model study in our series shows that managing HCV in prisons can make a substantial contribution to reducing transmission in the community [20].…”
mentioning
confidence: 75%
“…partmental models has been studied before, e.g. Martin et al (2011Martin et al ( , 2013; Gountas et al (2017) and Fraser et al (2018). Often, HCV transmission models implicitly assume that everyone in the PWID population is currently injecting drugs (active) and that everyone who is infected is diagnosed.…”
Section: Modelling Of Hcv Transmission Among Pwids and The Impact Of mentioning
confidence: 99%